2022
DOI: 10.3390/ma15165670
|View full text |Cite
|
Sign up to set email alerts
|

Driving Third-Order Optical Nonlinearities in Photoluminescent Si Nanoparticles by Nitrogen Co-Implantation in a Silica Matrix

Abstract: The photoluminescence and third-order nonlinear optical effects of co-implanted silicon nanoparticles and nitrogen ions in a silica matrix were studied. Experimental evidence shows the potential of nitrogen ions for changing optical properties exhibited by silicon nanoparticles implanted in an integrated system. The modification of the optical bandgap and photoluminescent intensity in the studied nanomaterials by the incorporation of nitrogen was analyzed. Standard two−wave mixing experiments were conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…As explained in Chapter 1.2, according to our earlier results on the fabrication, the optical gratings by implantation through a mask, lateral straggling rendered the finest diffraction gratings of a grating constant of 4 μm quasi-sinusoidal. 33 Since the lateral dimensions of the ion microbeams used in our actual experiments were in the range of 1.5−2.4 μm, we could expect quasi-sinusoidal grating profiles when writing "binary" gratings with the microbeams. In other words, writing single stripes separated by a grating constant of 3−5 μm would result in quasi-sinusoidal grating profiles.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…As explained in Chapter 1.2, according to our earlier results on the fabrication, the optical gratings by implantation through a mask, lateral straggling rendered the finest diffraction gratings of a grating constant of 4 μm quasi-sinusoidal. 33 Since the lateral dimensions of the ion microbeams used in our actual experiments were in the range of 1.5−2.4 μm, we could expect quasi-sinusoidal grating profiles when writing "binary" gratings with the microbeams. In other words, writing single stripes separated by a grating constant of 3−5 μm would result in quasi-sinusoidal grating profiles.…”
Section: Resultsmentioning
confidence: 96%
“…It was found that the implantations did not increase the absorption of the glass samples at visible wavelengths. Based on the measured amplitudes of the surface relief gratings and the diffraction efficiencies, and on the comparison of the implantation parameters of the actual experiment to the previous ones, where implantation through mask was performed, 33 it was concluded that the strength of the implanted index-of-refraction gratings was negligible compared to that of the surface relief one. Diffraction efficiency measurements were repeated with the incoming laser beam polarized parallel to the plane of incidence.…”
Section: Microprofilometric Study Of the Gratings And Analysis Of The...mentioning
confidence: 92%
See 2 more Smart Citations
“…According to ref. 26, instant changes in nonlinear optical properties occur promoted by nitrogen irradiation. The incorporation of N inside the host matrix containing the SiNPs slightly changes the effective optical bandgap of the nanocomposite from 4.5 eV to 4.9 eV.…”
Section: Introductionmentioning
confidence: 99%